Evaluation of ASSERT-PV V3R1 against the PSBT Benchmark - Kenneth H. Leung; David R. Novog (Science and Technology of Nuclear Installations)
Void fraction and DNB calculations conducted using ASSERT-PV V3R1 are evaluated against data from the NUPEC database as part of the OECD/NEA Pressurized Water Reactor Subchannel Benchmark Tests (PSBT). Void fraction measurements were well represented in the isolated single subchannel cases, with 77.0% of all predicted values falling within ±2σexp =0.06 of the experimental value. In the B5 type bundle, an average void fraction error of ϵ-α=-0.0540 was reported at the lower elevation, while this value was ϵ-α=-0.0405 at the upper measurement location. ASSERT was able to predict the steady state DNB power of the bundles to within ±10% of the measured value for a total of 344 times out of 432. Sensitivity studies conducted indicate that the Ahmad correlation with the Groeneveld 1995 CHF lookup table yielded the most accurate results, although some data points fell within the limiting quality region where the accuracy was reduced.